Clinical Evaluation of Remineralizing Agents in Children with Hypomineralized First Permanent Molars - Pani, Pooja; Ghosh, Ipsita; Choudhury, Shatabdi; Das, Rangana; Das, Ujjayan; Saha, Kanta (Journal of Neonatal Surgery, 2025)
Pediatric dentistry now requires clinical assessment of remineralising drugs for children with hypomineralized first permanent molars, especially because to the increased frequency of molar incisor hypomineralization. First permanent molars with low mineral content are more susceptible to caries, sensitive, and mechanically compromised, which can harm a child's dental health and quality of life. Remineralization with casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), fluoride varnishes, calcium glycerophosphate (CaGP), and other calcium phosphate-based compounds can repair molar incisor hypomineralization (MIH) related enamel defects without surgery. These remineralising agents will be clinically tested to improve the mineral content and structural integrity of hypomineralized first permanent molars in children. In-situ and in-vivo investigations assessed the effectiveness of remineralization therapies over time. Both fluoride-based and calcium phosphate formulations improved enamel remineralization, with CPP-ACP and CaGP showing excellent outcomes in mineral content and hypersensitivity. These medicines also reduced lesion size and severity, suggesting they might treat MIH abnormalities. However, the study stressed the need for longer follow-ups and bigger sample numbers to further understand these remineralising drugs' long-term efficacy and therapeutic application techniques. These results suggest that remineralising drugs, especially calcium phosphate-containing ones, may be a potential non-invasive therapy for hypomineralized first permanent molars.